2014
DOI: 10.1371/journal.pone.0089455
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma Brain-Derived Neurotrophic Factor and Vascular Endothelial Growth Factor Concentrations during Military Training

Abstract: Decreased concentrations of plasma brain-derived neurotrophic factor (BDNF) and serum BDNF have been proposed to be a state marker of depression and a biological indicator of loaded psychosocial stress. Stress evaluations of participants in military mission are critically important and appropriate objective biological parameters that evaluate stress are needed. In military circumstances, there are several problems to adopt plasma BDNF concentration as a stress biomarker. First, in addition to psychosocial stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 37 publications
2
32
0
6
Order By: Relevance
“…Our findings are consistent with a hypothesis by Giese and colleagues who suggested that chronic impairments in sleep are paralleled by reductions in BDNF levels as evidenced by lower plasma BDNF levels exhibited in individuals with insomnia [22]. Further, a recent study of individuals undergoing military training for 9 weeks exhibited reduced sleep quality and quantity and plasma BDNF levels further supporting the idea that CSR induces attenuations in BDNF [23]. …”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with a hypothesis by Giese and colleagues who suggested that chronic impairments in sleep are paralleled by reductions in BDNF levels as evidenced by lower plasma BDNF levels exhibited in individuals with insomnia [22]. Further, a recent study of individuals undergoing military training for 9 weeks exhibited reduced sleep quality and quantity and plasma BDNF levels further supporting the idea that CSR induces attenuations in BDNF [23]. …”
Section: Discussionsupporting
confidence: 92%
“…For example, it appears that acute and regular exercise leads to a broad variety of physiological changes such as an increased secretion of brain-derived neurotrophic factor [50,51] which may have a positive influence on sleep [52]. However, performing exercise in association with loaded psychosocial stress and decreased sleep quantity/quality may lead to decreases in plasma brain-derived neurotrophic factor [53]. Future studies on the relationship between evening exercise, level of stress, neurotrophic factors and subsequent sleep are warranted.…”
Section: High-intensity Exercise and Sleepmentioning
confidence: 99%
“…It was already demonstrated that Concord grape juice is beneficial to reverse the course of neuronal and behavioral aging in rats (Shukitt-Hale et al 2006), and in humans this juice was capable to improve the memory and cognitive function for older adults with early memory decline (Krikorian et al 2010) and also in older adults with mild memory decline (Krikorian et al 2012). BDNF is a dimer protein that plays an important role in neuroplasticity and neuronal maturation (Poo 2001, Suzuki et al 2014 as well exert an important role in both learning and memory abilities (Binder and Scharfman 2004). It is found throughout the brain, especially in some specific regions like the hippocampus (Binder and Scharfman 2004).…”
mentioning
confidence: 99%